Sensing Error in Respironics Continuous Positive Airway Pressure Machine Risks Compromising Patient Compliance - Robert A. Lowe; Joshua Ramseyer (Annals of Internal Medicine: Clinical Cases)
We report a continuous positive airway pressure (CPAP) machine malfunction that may compromise patient compliance. A patient's Respironics DreamStation machine (Philips Respironics) was observed to sense “vibratory snore” events incorrectly, resulting in pressure increases that led to poor mask fit, large air leaks, and patient discomfort. A replacement machine developed the same problem. Once aware of the defect, we observed it in 2 other patients. The manufacturer acknowledges receiving a few similar reports, but our experience suggests that this may be an underreported defect. The resulting increased pressures reduce patient tolerance for CPAP. This may be an unrecognized cause for patients abandoning CPAP therapy.